Chrystocentryczny wymiar postu i umartwienia w pismach św. Hieronima ze Strydonu - Sienkiewicz, Edward Jan (Vox Patrum, 2020)
Jerome of Stridon is most often presented as a great exegete, expert and translator of the Bible. Sometimes, we are also reminded of his significant achievements in theological dispute. Meanwhile, in his numerous writings and activities, Jerome presents himself to contemporaries and the following generations as an ascetic person who is very demanding of himself and of others. Practicing the monastic lifestyle in the desert and devoting himself to scientific work, he sought to know Jesus Christ as best as possible, to imitate Him as much as possible and unite with Him through his personal experiences. Therefore, he considers these two paths, i.e., the study of the Bible and penance and renunciation as the best ways to achieve that; besides – as he often emphasizes – these tow paths condition and support each other. In his ascetic theology, there are topics related to the deserving character of Christian mortification. Jerome sees the basis of in his very clear eschatological bias, which is fundamental to his assessment of the vanity of all that is temporal in relation to what is eternal and spiritual. The idea of the Kingdom of God, understood by him in a Christocentrical way and already present in temporality, becomes the essential argument for having Christians live lives that properly and fully realize this reality in Heaven. In his opinion, this is best served by renunciation up to the point of sacrificing one’s life. And this is best explained by the way of the Saviour, who calls on people to live with Him in the glory of Heaven by sharing His mortification.